Managing scientific information and research data - Baykoucheva, Svetla (Chandos Publishing, 2015)
Innovative technologies are changing the way research is performed, preserved, and communicated. Managing Scientific Information and Research Data explores how these technologies are used and provides detailed analysis of the approaches and tools developed to manage scientific information and data. Following an introduction, the book is then divided into 15 chapters discussing the changes in scientific communication; new models of publishing and peer review; ethics in scientific communication; preservation of data; discovery tools; discipline-specific practices of researchers for gathering and using scientific information; academic social networks; bibliographic management tools; information literacy and the information needs of students and researchers; the involvement of academic libraries in eScience and the new opportunities it presents to librarians; and interviews with experts in scientific information and publishing.Promotes innovative technologies for creating, sharing and managing scientific contentPresents new models of scientific publishing, peer review, and dissemination of information Serves as a practical guide for researchers, students, and librarians on how to discover, filter, and manage scientific informationAdvocates for the adoption of unique author identifiers such as ORCID and ResearcherID Looks into new tools that make scientific information easy to discover and manageShows what eScience is and why it is becoming a priority for academic libraries Demonstrates how Electronic Laboratory Notebooks can be used to record, store, share, and manage research dataShows how social media and the new area of Altmetrics increase researchers’ visibility and measure attention to their researchDirects to sources for datasetsProvides directions on choosing and using bibliographic management tools Critically examines the metrics used to evaluate research impact